Upaya Perempuan Single Parent dalam Menanamkan Sikap Disiplin Belajar pada Anak Remaja di Desa Bangunjaya Kecamatan Pakel Kabupaten Tulungagung - Gana Syakila; Ikfi Khoulita (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research is based on single parent women who play a dual role as housewives and work in place of their husbands. Despite this, single parent women are generally still able to meet their family's needs both in terms of economics, education and also attention to their children. This is an award in itself for single parent women. The research focus in writing this thesis is. 1.) What are the problems faced by single parent women in instilling a disciplined attitude towards learning in teenagers in Bangunjaya Village, Pakel District, Tulungagung Regency? 2.) What efforts are made by single parent women to instill a disciplined attitude towards learning in teenagers in Bangunjaya Village, Pakel District, Tulungagung Regency? The aim of the research is 1. To analyze the problems faced by single parent women in instilling a disciplined attitude towards learning in teenagers in Bangunjaya Village, Pakel District, Tulungagung Regency. 2. To analyze the efforts made by single parent women to instill a disciplined attitude towards learning in teenagers in Bangunjaya Village, Pakel District, Tulungagung Regency.The method used in this research is a qualitative approach with a descriptive qualitative research type. The location of this research is Bangunjaya Village, Pakel District, Tulungagung Regency. Data sources taken use primary and secondary data. Data collection by observation, interviews and documentation. Data analysis in the form of the latest theory, presentation and drawing conclusions. Checking data validity. From the results of the data discussion, it can be seen that the results of this research are the first problems faced by single parent women in instilling a disciplined attitude towards learning in teenagers in Bangunjaya Village, Pakel District, Tulungagung Regency, namely their children who often have small arguments when asked to study and their children they often play on cellphones. There are also those who exhibit deviant behavior and some are victims of bullying and sometimes complain because their friends are always with their father figure but not with him. The second is the efforts made by single parent women to instill a disciplined attitude towards learning in children in Bangunjaya Village, namely they accompany their children to study, while they also confiscate children's cellphones so that children want to study. There are also those who provide punishment and guidance starting from the family, discipline through habits, discipline through organizations, discipline through educational tools such as extracurriculars at school.